ASSEMBLE AND STANDARIZED TWO POWER TESTS AND THE RELATCONSHIP BETWEEN SHORT DEFFENCE RANGE AND RETREAT IN HAND BALL - kaleal, masharaq (Journal of Physical Education, 2010)
In handball the player can not accomplish good a achieve meant without especial physical Abilities .the aim of the study are:A: assemble and standardized two power tests which help defensives playersB: identify the relationship between especial power and defensive skills the study used survey design with correlation.Subjects were students of some colleges of physical education In Iraq.The study came up with some results which are :the proposed tests showed effectiveness in identifying the correlations between the two variables the study recommended practice in explosive power because it is the most indication which reflect defenses skills .more over the study recommended using these tests in future projects and researches .